The Accountability of Financial Sector Supervisors : Principles and Practice - Taylor, Michael (IMF Working Papers; Working Paper ;, 2005)
Policymakers' uneasiness about granting independence to financial sector regulators stems to a large extent from the lack of familiarity with, and elusiveness of, the concept of accountability. This paper gives operational content to accountability and argues that it is possible to do so in a way that encourages and supports agency independence. The paper first elaborates on the role and purposes of accountability. Second, it shows that the unique features of financial sector supervision point to a more complex system of accountability arrangements than, for instance, the conduct of monetary policy. Finally, the paper discusses specific arrangements that can best secure the objectives of accountability and, thus, independence. Our findings have a wider application than financial sector supervision.